2010
DOI: 10.1111/j.1365-2664.2010.01829.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination services decline with distance from natural habitat even in biodiversity‐rich areas

Abstract: Summary1. There is considerable evidence for the negative impacts of habitat alteration on pollinators in highly disturbed regions of the world. However, it remains unclear whether these findings reflect a global crisis for crop pollination. Understanding the extent to which world agriculture is endangered by pollinator decline is essential if the economic valuation of nature is to be used to promote conservation. 2. We assess the susceptibility to pollinator limitation of one of the most important tropical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
188
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 35 publications
20
188
0
9
Order By: Relevance
“…There are still relatively few studies, however, that have measured the effects of local-scale management actions on pollination services. In those studies that do, landscape-scale variables overshadow the effects of local-scale management (e.g., Kremen et al 2002, Carvalheiro et al 2010. Thus there is a need for additional highly replicated studies that examine both local and landscape factors (such as those conducted by Holzschuh et al 2008 andGabriel et al 2010) and that study not only pollinator communities but also pollination services.…”
Section: Pollination Servicesmentioning
confidence: 99%
“…There are still relatively few studies, however, that have measured the effects of local-scale management actions on pollination services. In those studies that do, landscape-scale variables overshadow the effects of local-scale management (e.g., Kremen et al 2002, Carvalheiro et al 2010. Thus there is a need for additional highly replicated studies that examine both local and landscape factors (such as those conducted by Holzschuh et al 2008 andGabriel et al 2010) and that study not only pollinator communities but also pollination services.…”
Section: Pollination Servicesmentioning
confidence: 99%
“…Habitat area is often found to be positively linked to the services of pollination and pest control, and the provision of these services tends to decline as the distance to natural habitat increases (e.g. Carvalheiro et al, 2010;Garibaldi et al, 2011). More diverse habitats support higher abundance and diversity of beneficial species, so vegetation species richness, structural diversity and landscape diversity are correlated with pollination and pest regulation efficiency (e.g.…”
Section: Pollination and Pest Controlmentioning
confidence: 99%
“…All flowering plants observed were identified, and the total number of flowers per species per plot recorded. As mango is a hyperabundant flowering species, the total number of flowers was estimated by counting the number of open flowers of three randomly-selected inflorescences (Carvalheiro et al, 2010). The average was multiplied by the total number of inflorescences counted in the plot.…”
Section: Samplingmentioning
confidence: 99%
“…Previous studies have found that natural vegetation in the area is a source of both flower visitors (Carvalheiro et al, 2010(Carvalheiro et al, , 2012Geslin et al, 2016) and natural enemies of crop pests (Henri et al, 2015;Morgan et al, 2017) in mango fields. Mangos in turn have been shown to harbour pests that can spill over into natural vegetation (Moxley et al, 2017), and it is likely that pollinators, too, spill over into natural vegetation.…”
Section: Introductionmentioning
confidence: 99%